The COVID-19 Vaccine and the Future of International Laws in Business, Travel, and Trade - Lane, Melanie (American Journal of Trade and Policy, 2021)
Since COVID-19, the world has been constantly evolving to adapt. Finding a cure quickly became the focus worldwide which altered set approaches to intellectual property rights. Additionally, creating a controversial vaccine has led to several more questions for the future. With varying vaccines and standards throughout the world, travel, business, and trade may face new challenges which change the current systems.
Keywords: COVID; Doha declaration; intellectual property; travel; international business; trade; international law